Analisis Rantai Pasok Ketersediaan Bahan Baku Produk Pertanian Jenis Beras dengan Metode Supply Chain Operations Reference - Laeela Jauhara; Devi Tanggasari (Jurnal Teknologi dan Mutu Pangan, 2024)
Supply chain management affects the availability, sufficiency, and quality of raw material inventory. With effective supply chain management, the inventory will always be well-maintained, meeting the needs and demands when required, especially at UD. Fajar Samudra. The purpose of this research is to understand the supply chain management regarding raw material inventory at UD. Fajar Samudra using a descriptive qualitative research method that addresses in more detail the specific and in-depth issues studied at UD. Fajar Samudra. In qualitative research, the population and sample are referred to as informants (company executives, warehouse managers, and the three largest suppliers at UD. Fajar Samudra). The research results indicate that the supply chain management at UD. Fajar Samudra shows that the supply chain management has not been able to meet the raw material inventory due to several issues in the field. These issues include inadequate procurement of raw materials due to the selection of rice types that do not match the requirements, damaged rice quality due to distribution processes, and unfulfilled quantity needs or demands, leading to dissatisfaction among consumers, as measured by the Supply Chain Operations Reference (SCOR) performance metrics. The advice that can be given to UD. Fajar Samudra is to make improvements by conducting forecasting based on historical sales data, engaging suppliers that implement management information systems, and implementing line balancing to enhance production strategies.